Production and financial networks in interplay: Crisis evidence from supplier-customer and credit registers - Kenan Huremovic; Gabriel Jiménez; Enrique Moral-Benito; Fernando Vega-Redondo; José-Luis Peydró (ZBW – Leibniz Information Centre for Economics, 2020)
We show that bank shocks originating in the fi nancial sector propagate upstream and downstream along the production network and triple the impact of direct bank shocks. Our identi fication relies on the universe of both supplier-customer transactions and bank loans in Spain, a standard operationalization of credit-supply shocks during the 2008-09 global crisis, and the proposed theoretical framework. The impact on real effects is strong, and similarly so, when considering: (i) direct bank shocks to firms versus fi rst-order inter firm contagion; (ii) first-order versus higher-order network effects; (iii) downstream versus upstream propagation; (iv) firm-speci fic versus economy-wide shocks. Market concentration ampli fies these effects.
Keywords: D85; E44; E51; G01; G21; 330; networks; supply chains; shock propagation; credit supply; real effects of finance